Argentina: Ornamental meadow plants in the Institute of Floriculture - Bugallo, Veronica Lucia; Facciuto, Gabriela Rosa (Floraldaily, 2023)
Sustainable landscaping proposes systems that reduce energy consumption, minimizing the carbon footprint. The possibility of replacing the traditional lawn with an ornamental meadow composed of spontaneous, native, and non-native vegetation constitutes one of the most beneficial design opportunities for the environment. These systems require less investment in maintenance by reducing the energy involved in the periodic mowing of the grass, its fertilization, and watering. In addition, this kind of environment increases the supply of food and provides shelter for insects and small animals, favoring biodiversity.